Biocarvões como condicionadores do solo e seus efeitos sobre o crescimento e a nutrição de Eucalyptus urograndis - Santos, Danilo Andrade (2020)
The State of Espírito Santo Brazil has, within its agrarian production, materials that are generated in great volume and with the potential to be used for energy conversion and consequent production of biochars to return to the field as soil condition